2011
DOI: 10.1007/s11103-011-9791-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression and β-glucan binding properties of Scots pine (Pinus sylvestris L.) antimicrobial protein (Sp-AMP)

Abstract: Scots pine (Pinus sylvestris) secretes a number of small, highly-related, disulfide-rich proteins (Sp-AMPs) in response to challenges with fungal pathogens such as Heterobasidion annosum, although their biological role has been unknown. Here, we examined the expression patterns of these genes, as well as the structure and function of the encoded proteins. Northern blots and quantitative real time PCR showed increased levels of expression that are sustained during the interactions of host trees with pathogens, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 43 publications
(39 reference statements)
2
23
0
Order By: Relevance
“…Our earlier results showed strong Sp-AMP induction in Scots pines challenged with the necrotrophic fungal pathogen H. annosum [20,21], justifying further detailed functional analyses of the corresponding gene. A successful transfer of a Sp-AMP2-encoding gene of the gymnosperm (Scots pine) to the angiosperm recipient (tobacco) was demonstrated.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Our earlier results showed strong Sp-AMP induction in Scots pines challenged with the necrotrophic fungal pathogen H. annosum [20,21], justifying further detailed functional analyses of the corresponding gene. A successful transfer of a Sp-AMP2-encoding gene of the gymnosperm (Scots pine) to the angiosperm recipient (tobacco) was demonstrated.…”
Section: Discussionsupporting
confidence: 57%
“…In Scots pine, increased expression of Sp-AMP in response to pathogen challenge, salicylic acid, ethylene, and other environmental stresses was shown in our earlier study [21]. SA-dependent signaling pathway, which is engaged with the cell death machinery against biotrophic pathogens, controls the synthesis of low molecular weight antimicrobial proteins such as PR-1, PR-2, and PR-5.…”
Section: Discussionsupporting
confidence: 50%
“…Purified MiAMP1 exhibits broad-spectrum inhibitory activity against several plant-pathogenic fungi, oomycetes, and gram-positive bacteria in vitro (Marcus et al 1997). Although a specific mode of action has not yet been determined (Stephens et al 2005), more functional information is available for Sp-AMP3, a homolog of MiAMP1 from the Scots pine Pinus sylvestris (Asiegbu et al 2003;Sooriyaarachchi et al 2011). Purified Sp-AMP3 protein has antifungal activity against the root-rotting Basidiomycete Heterobasidion annosum and, as part of this, causes morphological changes in the hyphae and spores of this fungus (Sooriyaarachchi et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although a specific mode of action has not yet been determined (Stephens et al 2005), more functional information is available for Sp-AMP3, a homolog of MiAMP1 from the Scots pine Pinus sylvestris (Asiegbu et al 2003;Sooriyaarachchi et al 2011). Purified Sp-AMP3 protein has antifungal activity against the root-rotting Basidiomycete Heterobasidion annosum and, as part of this, causes morphological changes in the hyphae and spores of this fungus (Sooriyaarachchi et al 2011). Carbohydratebinding assays revealed that Sp-AMP3 binds to both soluble and insoluble b-1,3-glucans but not to insoluble chitin or chitosan (Sooriyaarachchi et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Scots pine exhibits a range of constitutive and inductive defense responses, including the induction of traumatic resin ducts, lignification of infected tissues and production of other antimicrobial compounds, including PR (pathogenesis-related) proteins (Pearce 1996;Eyles et al 2010). The expression of PR-proteins is a key mechanism of pine seedling defense against pathogens, because the lack of powerful mechanical barriers cannot provide required protection against infection (Adomas 2007;Kovaleva et al 2009;Sooriyaarachchi et al 2011).…”
Section: Introductionmentioning
confidence: 99%